2021
DOI: 10.1007/s13202-021-01143-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anionic and non-ionic surfactant performance for Montney shale gas hydraulic fracturing fluids

Abstract: Hydraulic fracturing is often used in unconventional shale reservoirs, and 50%–95% of the injected hydraulic fracturing fluid remains in the formation due to the capillary effect. This phenomenon has been observed in the Montney shale formation, Canada, where the flowback water recovery is generally less than 25%. Surfactant is one of the hydraulic fracturing fluid additives for reducing surface tension and capillary forces to facilitate water flowback recovery. Surfactant loss due to adsorption by the reservo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…However, it is important to recognize that the selection and use of surfactants is quite system dependent and not always straightforward. While it has been demonstrated that the use of surfactants can aid flowback (Chai et al, 2019; Chee et al, 2021; Hussien et al, 2019; Somasundaran & Zhang, 2006), careful selection is required (Tangirala & Sheng, 2018), especially in unconventional shale plays (Yongjun et al, 2018), as poor selection can damage the formation. In some cases, performance can be dependent on factors that are not immediately obvious.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to recognize that the selection and use of surfactants is quite system dependent and not always straightforward. While it has been demonstrated that the use of surfactants can aid flowback (Chai et al, 2019; Chee et al, 2021; Hussien et al, 2019; Somasundaran & Zhang, 2006), careful selection is required (Tangirala & Sheng, 2018), especially in unconventional shale plays (Yongjun et al, 2018), as poor selection can damage the formation. In some cases, performance can be dependent on factors that are not immediately obvious.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic fracturing for stimulating production of low-permeability shale gas reservoirs uses large volumes of water, often exceeding 10 4 m 3 per well, while competing for valuable water resources and incurring high costs for water supply and treatment of flowback water. In addition to these burdens, loss of water-based fracturing fluids into reservoir matrix rocks during shut-in impedes production through blocking pores and through structural damage within the wetted fracture-matrix interface zone. ,− The adverse effects of water imbibition into shales have motivated investigations on ways to minimize water loss within reservoirs through manipulating interfacial properties and capillary forces. Indeed, a key strategy advanced in stimulating unconventional gas reservoirs is to use surfactants in hydraulic fracturing fluids in order to reduce the capillary pressure driving imbibition and thereby decrease thicknesses of water-blocked zones at the fracture-matrix interface. Indeed, in enhanced oil recovery (EOR), the applications of surfactants to reduce surface tension, stabilize microemulsions, and alter reservoir wettability to facilitate oil mobilization are well recognized. It is worth noting that surfactants are also added into hydraulic fracturing fluids for controlling rheological properties. As essential components of foams and gelling agents, surfactants can help enhance viscosity, thereby increase fracture width and improve proppant delivery. …”
Section: Introductionmentioning
confidence: 99%